Does localized control of invasive eastern gambusia (Poeciliidae: Gambusia holbrooki) increase population growth of generalist wetland fishes?. (2nd September 2013) - Tonkin, Zeb; Ramsey, David S. L.; Macdonald, Jed; Crook, David; King, Alison J.; Kaus, Andrew
Abstract While invasive fish management is heavily focussed on containment measures when introductions occur, examples from invasive species management in terrestrial systems suggest that there may also be considerable conservation benefits in implementing localized control programmes. We conducted a field‐based experiment to assess the effectiveness of removing a globally significant invasive fish, eastern gambusia Gambusia holbrooki, from natural wetland habitats of south‐eastern Australia. With recent work suggesting the impacts of eastern gambusia may be minimal for species with generalist life‐history strategies, we hypothesized that the removal of eastern gambusia will reduce localized population growth of the invasive species, but will have little influence on the population growth of more generalist sympatric wetland fish species. We used a predictive modelling approach to investigate changes in eastern gambusia populations following removal activities, and how sympatric fish species responded to such changes. Although eastern gambusia rapidly populated habitats, we demonstrated that control actions substantially reduced the rate of population increase over the four‐month study period. This suggests that control may be an effective localized strategy to suppress eastern gambusia densities. There was however, no evidence of any response to the removal actions by any of the three sympatric fish species investigated – carp gudgeon (Hypseleotris spp.), Australian smelt (Retropinna semoni) and the invasive common carp (Cyprinus carpio). These results support previous work which suggests that the flexible life‐history strategies and behavioural traits of all three species allow co‐existence with eastern gambusia. The study highlights the importance of understanding the potential outcomes of control options which is particularly pertinent for established aquatic invasive species where information on control effectiveness, population dynamics and/or ecosystem response is currently lacking.